1999
DOI: 10.1063/1.125353
|View full text |Cite
|
Sign up to set email alerts
|

An oxide-diluted magnetic semiconductor: Mn-doped ZnO

Abstract: Epitaxial thin films of an oxide-diluted magnetic semiconductor, Mn-doped ZnO, were fabricated by pulsed-laser deposition technique. Solubility of Mn into ZnO exceeds thermal equilibrium limit as a result of nonequilibrium film growth process. As Mn content is increased, the lattice constants of both a and c axes of wurtzite Zn1−xMnxO films (x<0.35) increase and the band gap expands although considerable in-gap absorption develops. Itinerant electrons over 1019 cm−3 can be doped into the Zn1−xMnxO films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
356
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 690 publications
(400 citation statements)
references
References 13 publications
42
356
1
1
Order By: Relevance
“…All data were corrected for the diamagnetism of the substrate and sample holder. Figure 1a shows electronic absorption spectra of a 0.10 M DMSO solution of 2% 17,22,37,38 The solid line in Figure 1a shows the spectrum collected after 1.65 equiv of base were added. Base addition beyond ca.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All data were corrected for the diamagnetism of the substrate and sample holder. Figure 1a shows electronic absorption spectra of a 0.10 M DMSO solution of 2% 17,22,37,38 The solid line in Figure 1a shows the spectrum collected after 1.65 equiv of base were added. Base addition beyond ca.…”
Section: Methodsmentioning
confidence: 99%
“…2, 3 Many earlier studies of Mn 2+ :ZnO revealed only paramagnetism, or at best ferromagnetism below RT, with T C ranging from 37 K to 250 K, and many have low saturation moments indicative of only partial magnetic ordering. 10,[16][17][18] The wide range of magnetic properties displayed by this and other ZnO DMSs prepared by apparently similar methods 10,19 suggests that the criteria necessary for ferromagnetism are highly sensitive to the preparation conditions and ultimately to the materials composition. Developing reproducible methods for preparing high-T C ferromagnetic DMSs is essential for their use in spintronics technologies but remains a central challenge in this field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Most of the experimental results show that, among transition-metal dopants, Co-doped ZnO systems are ferromagnetic in both thin films as well as bulk materials. 13,16,27 Also, there have been few reports of ferromagnetism in Mn-, 28,29 Ni-, 30 and some other TM-doped 31 ͑such as Cr or V͒ ZnO. The ferromagnetism in the Mn-doped system is yet to be understood, as Mn in the +2 valence state does not dope any carrier into the ZnO system and hence, by first-principles studies, 24 must lead to an antiferromagnetic ground state.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that Mn has higher solubility in ZnO thin fi lms grown by pulsed laser deposition (PLD), which is a non-equilibrium process [11]. Fabrication of Mn-doped ZnO thin fi lms without manganese oxides can facilitate the investigation and understanding of the magnetic properties of this material.…”
mentioning
confidence: 99%